How does religiosity influence gambling? A cross‑cultural study between Portuguese and English youth - Calado, F.; Vernon, M.; Nuyens, F.; Alexandre, J.; Griffiths, M. D. (Journal of Gambling Studies, 2024)
Research has shown that religion can play a protective role in diverse risky behaviors among young people. However, very little is known about the effect of religion in gambling, especially among young problem gamblers. A strong moral belief regarding gambling may prevent adolescents and young adults engaging in gambling and developing problems. Nevertheless, some evidence suggests that religion might have an influence on gambling cognitive distortions (i.e., some religious beliefs might influence the conceptions of chance and luck, which may contribute to an increase in gambling participation). The present study examined the different effects that religion can have on gambling behavior, in two different cultural contexts (i.e., Portugal and England), characterized by different religious affiliations. A sample (n = 725) comprising Portuguese (n = 312) and English (n = 413) adolescents and young adults completed an online survey. The findings indicated that Portuguese youth were more religious than their English counterparts. Moreover, religiosity was associated with lower gambling engagement among participants in both samples. Mediation analyses also showed that the cognitive distortion of illusion of control mediated the relationship between religiosity and problem gambling among the Portuguese participants, and the interpretative bias was a significant mediator in the English sample. The study’s findings suggest that religion can have a protective role on gambling behaviors. However, further research is needed to explore the interactive role of religion and cognitive distortions.